Dietary taurine stimulates the hepatic biosynthesis of both bile acids and cholesterol in the marine teleost, tiger puffer (Takifugu rubripes). Issue 12 (28th June 2020) - Xu, Houguo; Zhang, Qinggong; Kim, Shin-Kwon; Liao, Zhangbin; Wei, Yuliang; Sun, Bo; Jia, Linlin; Chi, Shuyan; Liang, Mengqing
Abstract: Taurine (TAU) plays important roles in the metabolism of bile acids, cholesterol and lipids. However, little relevant information has been available in fish where TAU has been identified as a conditionally essential nutrient. The present study aimed to investigate the effects of dietary TAU on the metabolism of bile acids, cholesterol and lipids in tiger puffer, which is both an important aquaculture species and a good research model, having a unique lipid storage pattern. An 8-week feeding trial was conducted in a flow-through seawater system. Three experimental diets differed only in TAU level, that is, 1·7, 8·2 and 14·0 mg/kg. TAU supplementation increased the total bile acid content in liver but decreased the content in serum. TAU supplementation also increased the contents of total cholesterol and HDL-cholesterol in both liver and serum. The hepatic bile acid profile mainly includes taurocholic acid (94·48 %), taurochenodeoxycholic acid (4·17 %) and taurodeoxycholic acid (1·35 %), and the contents of all these conjugated bile acids were increased by dietary TAU. The hepatic lipidomics analysis showed that TAU tended to decrease the abundance of individual phospholipids and increase those of some individual TAG and ceramides. The hepatic mRNA expression study showed that TAU stimulated the biosynthesis of both bile acids and cholesterol, possibly via regulation of farnesoid X receptor and HDL metabolism. TAU also stimulated the hepatic expression of lipogenic genes. In conclusion, dietary TAU stimulated the hepatic biosynthesis of both bile acids and cholesterol and tended to regulate lipid metabolism in multiple ways.